DESIGNING PLASTIC CUPES RING CUTTING MACHINE TO INCREASE PRODUCTIVITY - Achmad Wibolo; I Nengah Ludra Antara (Logic : Jurnal Rancang Bangun dan Teknologi, 2018)
The existence of plastic makes the society’s lives easier and more practical. Recently, the various kinds of products are made from this material because the votes are more durable. Plastics also give a negative effect for the environment such as soil pollution. The purpose of designing this plastic cup ring cutting machine is to sort the kind of plastics and to accelerate the process of plastic recycling, so that the plastic processing can be done faster. The authors designed a plastic cup ring mowers with electric motor mover. The design concepts of this machine are the height of machine is: 90 mm of height with a width of 50 mm, frame in size of 50 mm x 50 mm made from angled steel. This machine uses two vertical cutting blades and one horizontal cutting blade. The activator which is used in this machine is an electric diesel 1/4 HP with the rotation speed of 1400 rpm, belt-V type A38 as a link of the diesel rotation to the spindle. It is used two pieces of cushions because the direction of the load presses is perpendicular to axis of the shaft. So it is used bearing type of UCF pillow block in the diameter of 75 mm. The cutting process is done in a standing position and the button is pressed manually by using manpower, so that the rotation can become stable. If using a machine the process of cutting a ring of plastic cup can be accelerated. Manually it can be produced approximately 5 pieces of plastic cups. But, if using a machine, it can be produced approximately14 pieces of plastic cups.